滚动轴承温度场研究的现状和展望 - 刘喆; 王燕霜 (Jixie chuandong)
Temperature rise and distribution status of high-speed rolling bearings are directly effect on the performance and life of the main shaft bearings’ system.The increasing of rolling bearing’s rotate speed may lead to rapid increasing of heat generation because of friction.If the heat cannot be radiated in good time and effectively,the temperature would rise exceptionally in the bearing.The exceedingly high temperature will lead the surface of internal parts of bearings to be burned,even to be broken down as a result of agglutination or seizure with each other,and the consequences are greatly severe.Therefore,as the rotating speed of main shaft bearings being increased,the temperature rise and distribution status have already been the important targets which need to be considered in the rolling bearings.The bearings in depth from three aspects separately which are heat generation mechanisms, heat transference processes and temperature distributions are analyzed and investigated.Moreover,the current research work and existent problem on thermal analysis of bearings by the home and overseas scholars is details discribed.Meanwhile,the expectation for the future research to the temperature field of rolling bearings is given.